Nonstoichiometry as a source of magnetism in otherwise nonmagnetic oxides : magnetically interacting cation vacancies and their percolation (2007)
ABSTRACT: Recently, the possibility of inducing ferromagnetism in nonmagnetic insulators1–8 and in C60-based systems9–11 by creating intrinsic point defects, rather than by the more traditional approach of substitution by magnetic ions, has been discussed. Indeed, it appears that such observations of magnetism are invariably occurring in oxide samples having strong structural deviations from crystalline perfection, including heavily epitaxially textured samples and largesurface-area nanostructure grain boundaries, all associated with significant deviation from stoichiometry12,13. Here, we critically examine the conditions that may lead to such defect-induced ferromagnetism, following the general procedure we developed6 for CaO. Our approach is to first find the conditions leading to defect-induced magnetism under equilibrium. This will quantitatively establish the disparity between the defect concentration needed to establish equilibrium magnetism and what one would need to achieve experimentally with deliberate deviations from equilibrium. We outline four steps needed to determine if defect-induced magnetism is possible.